Separation of structurally related primary aliphatic amines using hydrophilic interaction chromatography with fluorescence detection after postcolumn derivatization with o‐phthaldialdehyde/mercaptoethanol. Issue 24 (28th December 2017) - Douša, Michal; Doubský, Jan
Abstract: The retention behavior of primary aliphatic amines (homologous series of aliphatic alkyl amines and cycloalkyl amines) and positional isomers of alkylamines in the hydrophilic interaction chromatography mode was studied. The study was carried out on a TSKgel Amide‐80 column followed by postcolumn derivatization with fluorescence detection to describe the retention mechanism of tested compounds. The effect of chromatographic conditions including column temperature, acetonitrile content in the mobile phase, mobile phase pH (ranging from 3.5 to 6.8), and salt concentration in the mobile phase was investigated. The final mobile phase consisted of acetonitrile and solution of 20 mM potassium formate pH 3.5 in ratio 80:20 v/v. The analyses were carried out at mobile phase flow rate of 1.0 mL/min and the column temperature of 20°C. The developed method was fully validated in terms of linearity, sensitivity (limit of detection and limit of quantification), accuracy, and precision according to International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use guidelines. The proposed new methods were proved to be highly sensitive, simple, and rapid, and were successfully applied to the determinations of isopropylamine, cyclohexylamine, and cyclopropylamine in relevant active pharmaceutical ingredients.